IMPROVING MATHEMATICAL PROBLEM SOLVING ABILITIES OF THE STUDENT WITH THE PROBLEM-BASED LEARNING APPROACH - Lisa Virdinarti Putra; Ela Suryani; Ontya Sekar Kinasih; Wahyu Tyas Utami (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
This study aimed to determine the application of the problem-based learning approach to improve the mathematics problem solving skills of the fifth grade students of SDN Susukan 04. The research was conducted at SDN Susukan 04. The method used in this study was the Plomp development model which consisted of three stages: (1) Preliminary Research; (2) Prototyping Phase; (3) Assessment Phase. The subjects in this study were students of class V SDN Susukan 04. The type of data in this study was quantitative. This quantitative data was obtained from the validation result score, the score of 10 students on the observation sheet and the learning material mastery test (TPBA) score. The validation phase of teaching materials developed with the Problem-based Learning approach and validation of the problem-solving ability test. Seeing what happened to students, it was necessary to strive the development of the teaching materials to improve problem-solving abilities in learning Mathematics with the Problem-based Learning approach, as the importance of solving abilities learning problems in teaching success. The test for the difference in the problem-solving ability test of the experimental class and the control class could be seen from the mean of the experimental class = 78.70> the mean of the control class = 64.76. So it can be concluded that the average problem-solving ability of the experimental class students were higher than the problem solving ability of control class students .